Correlations of the renin-angiotensin-system (RAS) gene polymorphisms with cardiac growth factors endothelin-1 and angiotensin II in high performance athletes - Graf, C.; Diet, F.; Palma-Hohmann, I.; Mahnke, N.; Böhm, M.; Rost, R; Predel, H. G. (European Journal of Sport Science, 2001)
Background: The regulation of myocardial mass in athletes involves complex interactions between physical stress, cardiac growth factors (GF), and the individual genetic background. Studies suggest the renin-angiotensin-system (RAS) plays a key role in the development of myocardial hypertrophy. Genetic polymorphisms of the RAS, associated with an activation, have been shown to correlate with left ventricular mass (LVM) in athletes. It is not clear whether these polymorphisms influence angiotensin (A) II levels directly or only markers coprecipitating with other factors modifying LVM. Endothelin (ET)-1 acts synergistically to AII in the induction of cardiac hypertrophy. The role of these GF in an athlete's heart is not yet clarified. Objectives: To analyze the correlation of RAS-gene polymorphisms with AII and ET-1 plasma concentrations in high performance athletes. Methods: In 83 male Caucasian, mainly endurance trained, elite athletes, intensity and duration of exercise were assessed by questionnaires; LVM was determined by 2-dimensional echocardiography. Plasma concentrations of AII and ET-1 were determined by radioimmunoassay. Results: LVM/LVMi significantly above reported average levels in sedentary persons was observed. AII plasma resting-concentrations correlated with the ACE gene polymorphism (p = .039), finding the highest levels in DD-athletes. There were no further correlations between the AII levels and the angiotensinogen gene polymorphisms, and the combined polymorphisms (p = .585, p = .162). ET-1 plasma levels did not correlate with any of the investigated parameters. No GF correlates with LVM/LVMi. Conclusions: The highest AII plasma resting concentrations were found in athletes homozygous to DD. This finding suggests a functional effect of the ACE I/D genotypes, possibly influencing cardiac growth in high performance athletes. The absence of a correlation with ET-1 plasma levels does not rule out its influence; local cardiac effects remain elusive. Further longitudinal studies under controlled exercise conditions are necessary.